Studies of adsorbed phenothiazine antidotes by temperature-programmed desorption with mass-spectrometric analysis - Kulik, T.V.; Galagan, N.P.; Pokrovskiy, V.A.; Khrapak, V.V. (Поверхность, 2002)
By spectrophotometric and kinetic methods of analysis a study has been made of adsorption of three antidotes of the phenothiazine series on the surface of fumed silica from water solutions. Physical and chemical parameters of adsorption have been calculated. Thermal decomposition of bulk antidotes has been investigated by the temperatureprogrammed desorption technique with the mass-spectrometric registration of volatile constituents (TPD MS) and the results achieved were compared with data for adsorbed samples. For all the samples at the first stage the maximum of HCl evolution is observed at 180°C. For methylene blue and toluidinee dark blue the first stage is accompanied by evolution of CH3Cl (m/z 50). Then the decomposition proceeds through the rupture of thiazine rings. At this stage, at the temperature of maximum 240°C and higher in mass spectra there appear lines at m/z 93, 66, 51 corresponding to molecular decomposition of aniline. Besides, sulfur-containing fragments originating from rupture of thiazine rings (lines at m/z 32, 34, 107, 121, 135) are observed among the lines attributed to products of thermal decomposition of methylene blue and toluidinee dark blue at high temperatures. Comparison of TPD MS experimental data about thermal decomposition of the antidotes in the condensed and adsorbed states has shown that adsorption on highly dispersed silica surface changed dramatically the mechanism of thermal transformations and increased thermal stability of antidote molecules in comparison to that in the condensed state.